ANALISIS KETERLAKSANAAN PRAKTIKUM BIOLOGI SEMESTER GANJIL 2024/2025 SMA NEGERI 1 GOWA - Arifah, Andi Iffah; Arsal, Andi Faridah; Syamsiah, Syamsiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Biology learning in schools still faces various obstacles, such as low motivation and activeness of students and the use of media and learning models that are less interesting. In addition, the implementation of laboratory practicums is also less than optimal due to limited facilities, time, and supporting staff, which has an impact on the low active participation of students in the learning process. This study aims to determine and describe the implementation of biology practicum activities at SMA Negeri 1 Gowa. This type of research is descriptive research using quantitative and qualitative approaches (mix method). Data were collected through filling out checklists, interviews, and documentation. The results of the study showed that the implementation of biology practicums at SMA Negeri 1 Gowa referring to the Learning Outcomes (CP) of the Independent Curriculum reached 68% with a fairly good category in the laboratory. The practicums carried out in class XI included observations of diffusion, osmosis, mitosis and meiosis, human skeletal torso, blood type, blood pressure, pulse rate, and starch and glucose tests, while those that were not carried out were calorie calculations on the 4 healthy 5 perfect menu, vitamin tests, and fat tests. There were several obstacles in the implementation of biology practicums, including several microscopes in poor condition (blurry), practicums were carried out in class due to schedules that clashed with other subjects, students did not yet understand the basics of implementing practicums, limited time and water, practicums coincided with school events, and the unavailability of guides and Student Worksheets (LKPD) in several classes. ABSTRAK Pembelajaran biologi di sekolah masih menghadapi berbagai kendala, seperti rendahnya motivasi dan keaktifan peserta didik serta penggunaan media dan model pembelajaran yang kurang menarik. Selain itu, pelaksanaan praktikum di laboratorium juga kurang optimal akibat keterbatasan fasilitas, waktu, dan tenaga pendukung, sehingga berdampak pada rendahnya partisipasi aktif peserta didik dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan keterlaksanaan kegiatan praktikum biologi SMA Negeri 1 Gowa. Jenis penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kuantitatif dan kualitatif (mix method). Data dikumpulkan melalui pengisian daftar periksa (check- list), wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa keterlaksanaan praktikum biologi di SMA Negeri 1 Gowa yang mengacu pada Capaian Pembelajaran (CP) Kurikulum Merdeka mencapai 68% dengan kategori cukup baik di laboratorium. Praktikum yang terlaksana di kelas XI meliputi pengamatan difusi, osmosis, mitosis dan meiosis, torso rangka manusia, golongan darah, tekanan darah, denyut nadi, serta uji amilum dan glukosa sedangkan yang tidak terlaksana adalah perhitungan kalori pada menu 4 sehat 5 sempurna, uji vitamin, dan uji lemak. Terdapat beberapa kendala dalam pelaksanaan praktikum biologi, di antaranya beberapa mikroskop dalam kondisi kurang baik (buram), praktikum dilaksanakan di kelas akibat jadwal yang bertabrakan dengan mata pelajaran lain, peserta didik belum memahami dasar-dasar pelaksanaan praktikum, keterbatasan waktu dan air, praktikum bertepatan dengan acara sekolah, serta ketidaksediaan penuntun dan Lembar Kerja Peserta Didik (LKPD) di beberapa kelas.